The risk of drinking water with excessive nitrate content by residents of different age categories of the Ternopil region. - Danchyshyn, M.; Lototska, O. (Journal of Education, Health and Sport, 2022)
Introduction Human health largely depends on the quality of the water he consumes. The impact of drinking water quality on public health depends on a number of factors. Thus, water pollution with above-normal concentrations of nitrates leads to the occurrence of water-nitrate methemoglobinemia in children, a decrease in the general resistance of the body, which contributes to an increase in the level of general morbidity, in particular, infectious and oncological diseases. It is reported that a positive correlation of the level of cardiovascular morbidity was found in the presence of nitrates. The aim of the study: to assess the risks of nitrate pollution of water from individual wells on the health of residents of different age groups in certain districts of the Ternopil region. Material and methods: the research was conducted in 5 districts of Ternopil region. A total of 1,495 samples of drinking water from individual wells were analyzed, the water from which is used to feed all segments of the population, including children and pregnant women.In order to assess the degree of risk of drinking water with excessive nitrate content for the health of the population of different age groups, the indicators of daily intake (ADD) of a chemical substance in the body of consumers and the hazard ratio (HQ) were calculated according to the method of risk assessment from exposure to chemical substances that pollute the environmentResults and discussion: According to the results of laboratory studies, the highest content of nitrates was found in the wells of the Zalishchytsky district - from 57.7 to 153.0 mg/dm3, in other districts the level fluctuated within the following limits: in Pidvolochysk - from 92.4 to 139.0 mg/dm3. Borshchivskyi - from 59.2 to 133.2 mg/dm3, Ternopilskyi - from 73.9 to 98.4 mg/dm3, and Terebovlyanskyi - from 50.5 to 57.8 mg/dm3. The calculated value of the average daily dose (ADD) of the intake of nitrates with drinking water to the body of residents of the above-described regions of the Ternopil region ranges from 2.5 to 7.7 for children; 1.6 - 4.8 - for teenagers (Table 1).; 1.9 - 5.1 for women and 1.8 - 4.9 for men. When assessing the risk to the health of the population, it was found that the hazard ratio at the minimum concentration of nitrates in drinking water determined by us was 1.5 for children, and 1.2 for teenagers. At the maximum concentration of nitrates, the HQ is 4.8 and 3.0, respectively, for children and adolescents. At the minimum concentration of nitrates in drinking water, the hazard ratio for women was 1.0; at the maximum concentration – 3.2. For men, the HQ is 1.0 and 3.0, for minimum and maximum nitrate concentrationsSummary: The risk of negative effects when drinking the same water is greater in children compared to other categories of the population.